JOB SATISFACTION AND MOTIVATION: PREDICTORS OF EMPLOYEE PERFORMANCE - et. al., Shrirang Altekar (International Journal of Modern Agriculture, 2021)
Organizations totally depend on their workforce for optimum results which is why they are known as the human capital of the company. Human resource is an essential part of the any organization, it can either take the organization to new heights, or the opposite if not managed properly. Our approach towards is to investigate the relationship of these variables on different employees by a secondary data collection approach among various business sectors and to find out how much these factors affect the job performance of an employee. Job Satisfaction refers to the positive feelings that an employee holds in his mind about his job. If the employee is not satisfied, he won’t be able to give his hundred percent towards his task whereas the satisfied employee would perform fruitful and consistent. Motivation refers to when a person is stimulated to accomplish his or her goal. It can either be by making them realize their responsibilities, offering them incentives/bonus or any other way they find beneficial for themselves. This Research study comprises of research sample of 203 employees. A structuredQuestionnaire was prepared to collect the data. Descriptive statistics analytical techniqueswere used to find out the relationship between the variables